Investigation of the Coeliac Trunk Morphometry with Multidetector Computed Tomography Angiography - Odabaşıoğlu, Mehmet Ercan; Cihan, Ömer Faruk; Yılmaz, Mehmet Tuğrul (European Journal of Therapeutics, 2021)
Objective: Accurate knowledge of vascular anomalies is critical in surgical interventions, radiology, and organ transplantation procedures. Vascular variations during these procedures can cause serious complications. This study aimed to evaluate the coeliac trunk (CT) and its branches morphometrically, to examine possible variations with multidetector computed tomographic angiography (MDCTA), and to compare the obtained data with the findings in the literature. Methods: In this study, abdominal MDCTA images of 126 people taken between April 2014 and April 2016 at Necmettin Erbakan University University Meram Medical Faculty Hospital were analyzed retrospectively. Variation and morphometric analysis of CT and its branches were performed. In the morphometric analysis, diameter measurements were made in centimeters (cm) and compared in terms of sex of the patients. Variation analysis was performed per a useful and simple classification we developed through a comprehensive literature review. Results: Diameter measurements of CT (0.73±0.13, p=0.002), splenic artery (0.69±0.1, p=0.0004), common hepatic artery (0.66±0.1, p=0.042), and left gastric artery (0.27±0.11, p=0.0001) were statistically significant in men than in women (p<0.05). In our study, type I (normal trifurcation pattern - complete) was detected in 111 (88.09%) cases, and variation was detected in 15 (11.91%) cases. The distribution of these variations is from the most common to the least; type II- (bifurcation-incomplete) 8 (6.34%), type V (additional branches) 5 (3.96%), type IV (coeliomesenteric trunk) 1 (0.79%) and 1 (0.79%) unidentified case. No type III (no CT) variation was found. Conclusion: Variations and anatomy of CT and its branches should always be taken into consideration in clinical studies, angiographic methods, and surgical interventions against possible complications